Listening in the silence, seeing in the dark : reconstructing life after brain injury - Johansen, Ruthann Knechel, 1942- (University of California Press, 2002)
Traumatic brain injury can interrupt without warning the life story that any one of us is in the midst of creating. When the author's 15-year-old son survives a car crash in spite of massive trauma to his brain, she and her family know only that his story has not ended. This title tells Ruthann Knechel Johansen's story.